Teknik Progressive Muscle Relaxtation Training (PMRT) Berbasis Islam untuk Mengatasi Kecemasan - Parhaen; Nurjannah (Program Studi Bimbingan dan Konseling Islam, 2024)
The purpose of this study is to offer an intervention to overcome anxiety by combining asmaul husna remembrance therapy and progressive muscle relaxation training techniques. Anxiety is a body reaction that generally occurs in every individual when facing danger. However, anxiety can be a problem if it occurs for a long time and without cause so that it can interfere with activities. Overcoming anxiety requires special techniques. In the western world and the Islamic world have different techniques in overcoming anxiety, but therapeutic techniques from the west and from Islam can be combined so that more effective results are obtained. This research uses qualitative literature study research. Researchers collect various kinds of reading materials both from books, or articles related to research as reference material in the preparation of articles so as to obtain the concept of morals in the thought of Islamic counseling guidance according to ibnu miskawaihThe Progressive Muscle Relaxtation Training technique is a technique to relax tense muscles that cause anxiety. However, anxiety does not only occur due to muscle tension, but also caused by negative thoughts. Asmaul Husna therapy is a therapy that provides suggestions to change negative thoughts into positive thoughts. Combining these two techniques is expected to provide higher effectiveness in reducing anxiety.